2023
DOI: 10.3390/ijms24108871
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Immunosuppressive Adenosine Signaling: A Review of Potential Immunotherapy Combination Strategies

Abstract: The tumor microenvironment regulates many aspects of cancer progression and anti-tumor immunity. Cancer cells employ a variety of immunosuppressive mechanisms to dampen immune cell function in the tumor microenvironment. While immunotherapies that target these mechanisms, such as immune checkpoint blockade, have had notable clinical success, resistance is common, and there is an urgent need to identify additional targets. Extracellular adenosine, a metabolite of ATP, is found at high levels in the tumor microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Metabolic modulators such as indoleamine 2,3-dioxygenase 1 (IDO) and adenosine can also play a role in fostering immunosuppressive conditions in the TME that result in immunotherapy resistance ( Figure 1d ). 104 , 122 , 123 IDO is an intracellular enzyme that catalyzes the reaction that converts tryptophan into kynurenine under normal physiological conditions. It is expressed only in select tissues (mucosal tissues, placenta, eye, and pancreas) and by a small population of immune cells (DCs and eosinophils).…”
Section: Underlying Mechanism Associated To Ici Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic modulators such as indoleamine 2,3-dioxygenase 1 (IDO) and adenosine can also play a role in fostering immunosuppressive conditions in the TME that result in immunotherapy resistance ( Figure 1d ). 104 , 122 , 123 IDO is an intracellular enzyme that catalyzes the reaction that converts tryptophan into kynurenine under normal physiological conditions. It is expressed only in select tissues (mucosal tissues, placenta, eye, and pancreas) and by a small population of immune cells (DCs and eosinophils).…”
Section: Underlying Mechanism Associated To Ici Resistancementioning
confidence: 99%
“…Adenosine accumulates in the TME through the conversion of hydrolyzed forms of adenosine triphosphate (ATP) to adenosine diphosphate (ADP) or adenosine monophosphate (AMP), and then into adenosine by ectonucleotidases (CD39 and CD73), which are overexpressed in different cancer types. 123 High levels of adenosine in the TME may also be due to mutations or hypoxic conditions that decrease the reduction of this metabolite ( Figure 1d ). 123 Another source of adenosine in the TME comes from nicotinamide adenine dinucleotide (NAD + ) converted to AMP by CD38, a molecule that is upregulated by tumor cells and identified as another mechanism of resistance to PD-1 and PD-L1 checkpoint blockade ( Figure 1d ).…”
Section: Underlying Mechanism Associated To Ici Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The effective killing of ADCC by NK cells and the restoration of non-malignant CD4 + and CD8 + T cell proliferation can both be achieved through inhibition of the CD39/CD73/ADO pathway [ 35 ]. Interestingly, NK cells show the highest amounts of A2A receptor expression, even though A2A receptors are found on the majority of immune cells [ 36 ]. Research has revealed that the A2A receptor functions as a checkpoint to restrict NK cell development by directly impeding NK cell maturation in the TME.…”
Section: How Tme Affects Metabolic Reprogramming Of Nk Cellsmentioning
confidence: 99%
“…Apart from immune suppression, it promotes tumor cell proliferation and metastasis by catabolic energy production [21]. Additionally, TAMs also exhibit high expression of ectonucleotidase that in turn consume ATP to generate adenosine, maintaining immunosuppression in TME [23] [24].…”
Section: Introductionmentioning
confidence: 99%